THE EFFECT OF TRAINING AND DEVELOPMENT ON EXECUTIVES’ PERFORMANCE IN MANUFACTURING FIRMS: A CASE STUDY AT KULIM-HI TECH PARK KULIM, KEDAH, MALAYSIA - Bokhori Md Amin (Galaxy International Interdisciplinary Research Journal, 2022)
Training and development are one of the human resource management practices that are very important in addressing issues related to job performance. Therefore, the purpose of this study is to assess the extent of the role of training and development and its contribution to the performance of executive work in manufacturing firms. Methodology in this study was built where a questionnaire was designed for data collection to measure training and development related orientation training, on-job training, off-job training, and ongoing training on executives ’performance. Data were collected among executives in manufacturing firms at Kulim Hi-tech Park, Kulim, Kedah, Malaysia which had a 4438 population, 351 samples, and 244 respondents successfully collected from 25 manufacturing firms. A stratified sampling method was used to collect data and the data obtained were analyzed using SmartPLS version 3.7.8. The finding of this study found that there is a significant relationship between off-job training and ongoing training on executives’ performance. While on-job training and orientation training are not-significant. It is proved from SmartPLS analysis shown that 2 independent variables have a positive impact on executives’ performance in manufacturing firms and 2 variables do not support executives’ performance. The limitation of the research only covers the manufacturing firms. Another limitation is the respondents only included executives. Apart from these limitations, this research can give a strong impact on the top management of manufacturing firms to design the strategy of training and development to be more effective in improving the work performance of executives.